The annual testicular cycle of the domestic quail (Coturnix coturnix japonica) - Artoni, SMBB; Orsi, A. M.; Carvalho, TLL; Lopes, R. A. (Blackwell Wissenschafts Verlag Gmbh, 1997)
A morphometric study was conducted on the testis of the domestic quail Coturnix coturnix japonica to determine testicular kinetics. We investigated the variability along the year of testicular parameters such as seminiferous tubule diameter, germinal epithelium height and amount of meiotic figures of maturing spermatids in the seminiferous epithelium and of sperm in the tubular lumen. The results of morphometric analysis showed the occurrence of an annual testicular cycle defined by four distinct phases: a resting phase (at the end of summer), a recrudescence phase (in the fall), a proliferative phase (at the end of winter and beginning of spring), and a regression phase (spring and summer). We also observed that the testes of adult quails present elevated and maximal spermatogenic activity in fall-winter (short-day period) and at the beginning of spring, respectively, and lower values in spring and summer (long-day periods), with minimum values at the end of summer.